SYNTHESIS OF CELLULOSE NANOCRYSTALS (CNCS) AS A SUPPORT MATRIX FOR LIPASE IMMOBILIZATION TO CONVERSION OF VEGETABLE OIL INTO FATTY ACID - Tresna Umi Culsum, Neng
Fatty acids are one of the key basic components utilized in a wide range of sectors, such as the production of soaps, detergents, food, cosmetics, pharmaceuticals, and green diesel precursor. The Colgate-Emery process is often used to hydrolyze oil or fat at a temperature of 250 °C and a pressure of 4.82 MPa to produce fatty acids. Despite being simple, the process has disadvantages in terms of energy usage and product purification. One strategy for lowering energy use and product thermal degradation is the hydrolysis of oil at lower temperatures and pressures using lipase as a biocatalyst. In order to reuse lipases and extend the useful life of enzyme catalysts in industry, they were immobilized on a support. In addition, the immobilized enzymes on the nanomaterial structure demonstrated high enzyme loading and improved stability. This study focuses on designing cellulose-based materials as a matrix for lipase immobilization to hydrolyze palm oil at a temperature of 40 °C and atmospheric pressure. The process started with synthesizing and characterizing cellulose nanocrystals (CNCs) from various biomasses, including sugarcane bagasse, rice straw, and empty fruit bunches of palm oil, by applying the TEMPO-mediated oxidation method. The CNCs product was characterized using X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Transmission Electron Microscopy (TEM), and Thermogravimetric Analysis (TGA). According to the results, CNCs produced from sugarcane bagasse had a crystallinity of 72% with an average length of 104????64 nm, and CNCs produced from rice straw had a crystallinity of 73% with an average length of 102????34 nm. CNCs produced from OPEFB had a crystallinity of 65% with an average length of 157????27 nm. The crystallinity of CNCs increases with increasing oxidizing concentration. This occurrence can be caused by the greater the amount of oxidizing agent, the more amorphous parts are removed. In addition, the results of the FTIR analysis revealed the presence of a carbonyl group (C=O) arising from the carboxylate group, which indicates that the hydroxyl group at the primary C6 position of cellulose has been oxidized to a carboxylate group. The CNCs products were used for lipase immobilization. The research was conducted to determine the effect of CNCs type, lipase concentration, immobilization time, and the ratio of EDC/CNCs on the activity of immobilized lipase. The results showed that lipase immobilized on CNCs from rice straw produced the highest relative activity of 71%. This occurrence was related to the characteristics of CNCs, including the content of carboxyl groups on the CNCs surfaces, the size of the CNCs, crystallinity, and the composition of the raw materials used for synthesizing CNCs. Therefore, CNCs produced from rice straws were selected to be used in the optimization of immobilization conditions. As a result, the optimum immobilization conditions were obtained at a lipase concentration of 1.5 mg/mL, an immobilization time of 2 hours, and a CNC/EDC ratio of 1:3. Additionally, the thermal stability of immobilized lipase increased at temperature 40 °C compared to free lipase due to increased lipase stiffness after covalently bonding to CNCs. Lipases that have been successfully immobilized on CNCs were used to hydrolyze palm oil. The use of Arabic gum with a concentration of 5% shows positively affected lipase activity, which could be attributed to an increase in the interfacial area of the oil emulsion and the stabilization of the emulsion. Moreover, the highest percentage of hydrolysis was achieved at pH 8 of 9.5%. Changes in pH can affect the strain on the "lid" of lipase to open or close the catalytic core, which can bind to the substrate. The reusability of immobilized lipase was conducted five times by maintaining only 27% of the initial activity. In addition, research was performed to determine the kinetic parameters of palm oil hydrolysis using immobilized lipase. The agitation was varied from 150 to 200 rpm to ensure the determination of kinetic parameters in the kinetic regime. Substrate concentrations (100–300 mM) and temperature (30–50 °C) were varied to obtain the initial rate using a batch reactor for 6 hours. The results revealed that the Michaelis-Menten model fitted with the experiment, and the kinetic parameters, including KM, Vmax, and Ea, could be determined. Immobilized lipase has the highest Vmax value at a temperature of 40 °C of 15.53 mM/hour with a KM of 99.80 mM and an Ea of 41.07 kJ/mol. Moreover, modeling was performed to select the suitable kinetic model using the three types of Michaelis-Menten models with substrate and product inhibition. The results show that hydrolysis of palm oil using immobilized lipase fits with the Michaelis-Menten model in the presence of product inhibition with a root mean squared error (RMSE) value of 0.13 and an inhibition constant (KI) value of 4 mM. The simulation results show that the semi-batch reactor can achieve a higher conversion at the beginning of the reaction with a conversion of 28% and can achieve the closest conversion to a batch reactor of 36% at a feed time of 10 hours